2020
DOI: 10.1002/rrq.336
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Element Model of Reading Instruction

Abstract: The science of reading emphasizes explicit skills‐based reading instruction to support students’ reading acquisition. Yet, despite ample evidence of support, some students do not respond to such instruction adequately. To characterize why some students are not responsive to evidence‐based reading instruction and to inform the development of novel instructional approaches for improving responsiveness, cross‐disciplinary perspectives on cognitive and academic development are important. Based on the cognitive–aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 91 publications
1
25
0
1
Order By: Relevance
“…Unlike other meta-analytic reviews, a random-effects model was used which provided a more methodologically defensible approach for integrating various effect sizes and as well as mixed-effects models for examining the influence of moderating variables. Overall, results were consistent with Melby-Lervåg and Hulme (2013) and suggested that WM Peng and Goodrich (2020)].…”
Section: Studysupporting
confidence: 86%
“…Unlike other meta-analytic reviews, a random-effects model was used which provided a more methodologically defensible approach for integrating various effect sizes and as well as mixed-effects models for examining the influence of moderating variables. Overall, results were consistent with Melby-Lervåg and Hulme (2013) and suggested that WM Peng and Goodrich (2020)].…”
Section: Studysupporting
confidence: 86%
“…We note, however, that not all EF interventions are effective for improving reading outcomes (for a review, see Jacob & Parkinson, 2015). Domain‐specific interventions—those tied to the specific demands of literacy tasks—are more effective than domain‐general EF interventions (Melby‐Lervåg & Hulme, 2013; Peng & Goodrich, 2020), a point that should be explored in future work with EB students.…”
Section: Discussionmentioning
confidence: 99%
“…Recent instructional models emphasize explicit skills-based reading instruction. For example, the cognitive-element instructional model emphasizes that outcomes should consist of near-transfer tasks (e.g., inferencing) instead of, or in addition to, far-transfer effects on general outcome measures of reading (Peng & Goodrich, 2020;Van Norman et al, 2018). In addition, instruction should be taskspecific and assimilated within existing skill-based reading activities.…”
Section: Implications For Interventionsmentioning
confidence: 99%